Unlocking the wasting enigma: Highlights from the 8th Cachexia Conference. Issue 1 (17th February 2016) - Ebner, Nicole; von Haehling, Stephan
Abstract: This article highlights pre‐clinical and clinical studies into the field of wasting disorders that were presented at the 8th Cachexia Conference held in Paris, France December 2015. This year some interesting results of clinical trials and different new therapeutic targets were shown. This article presents the biological and clinical significance of different markers and new drugs for the treatment of skeletal muscle wasting. Effective treatments of cachexia and wasting disorders are urgently needed in order to improve the patients' quality of life and their survival.